PERENCANAAN BAHASA BALI (MENGANTISIPASI KETERPURUKAN BAHASA, AKSARA, DAN SASTRA BALI) - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
As a mother tongue , the language of Bali should as a first language known by theyounger generation Bali . The reality is not like that , just a lot of the younger generation Balicould not communicate with the Balinese language is good and right. How could the youngergeneration can understand and ngalakoni Bali culture Bali , was the source language is notunderstood?Bali government should find a way out so that the people of Bali are not too far off therails cultural identity. One way is to make language planning Bali, so the Balinese languagewith the content value of high culture in it can permeate the ideological order of the Balinesepeople, so it can be used as an anticipatory measure refraction community character. Balilanguage planning include: planning in development terms, compose, research, and education.Keywords: Mother, Shift in Cultural Values, Ideology